Vaccination with inhibin-α provides effective immunotherapy against testicular stromal cell tumors - Robert Aguilar; Justin M. Johnson; Patrick Barrett; Vincent K. Tuohy (Journal for ImmunoTherapy of Cancer, 2017)
Abstract Background Testicular cancer is the most common male neoplasm occurring in men between the ages of 20 and 34. Although germ-line testicular tumors respond favorably to current standard of care, testicular stromal cell (TSC) tumors derived from Sertoli cells or Leydig cells often fail to respond to chemotherapy or radiation therapy and have a 5-year overall survival significantly lower than the more common and more treatable germ line testicular tumors. Methods To improve outcomes for TSC cancer, we have developed a therapeutic vaccine targeting inhibin-α, a protein produced by normal Sertoli and Leydig cells of the testes and expressed in the majority of TSC tumors. Results We found that vaccination against recombinant mouse inhibin-α provides protection and therapy against transplantable I-10 mouse TSC tumors in male BALB/c mice. Similarly, we found that vaccination with the immunodominant p215-234 peptide of inhibin-α (Inα 215-234) inhibits the growth of autochthonous TSC tumors occurring in male SJL.AMH-SV40Tag transgenic mice. The tumor immunity and enhanced overall survival induced by inhibin-α vaccination may be passively transferred into naive male BALB/c recipients with either CD4+ T cells, B220+ B cells, or sera from inhibin-α primed mice. Conclusions Considering the lack of any alternative effective treatment for chemo- and radiation-resistant TSC tumors, our results provide for the first time a rational basis for immune-mediated control of these aggressive and lethal variants of testicular cancer.